Rethinking Pedagogy Through Storytelling in School Mathematics - Nepal, Kamal; Shrestha, Indra Mani (Journal of Transformative Praxis, 2023)
This article focuses on storytelling as an alternative innovative pedagogical approach to teaching mathematics in response to a discipline-based pedagogy in the context of Nepali Mathematics Education. In Nepal (probably worldwide), mathematics teachers rarely teach mathematics for creating mathematics. Instead, they focus on teaching the steps to repeat someone else's creation without exploring how mathematics relates to students' life worlds. As a result, students feel mathematics as a dry subject, mathematics teachers as apathetic human beings and mathematics classrooms as a boring factory of producing passive learners. In this context, this paper explores how storytelling may become one of the many innovative mathematics pedagogies and help mathematics teachers rethink their pedagogical practices for teaching mathematics joyfully and meaningfully. We used autoethnography as a research methodology that portrayed the narratives of the first author extracted from his MPhil research based on storytelling pedagogy and the narratives of the second author based on his experiences of teaching the course at the post-graduate level and conducting teacher professional development training across Nepal. The research inquiry explored the connections of mathematics with students' life worlds through storytelling as a pedagogical approach.